Propuesta de implementación del sistema de gestión de seguridad y salud en el trabajo basado en la norma NTC ISO 45001:2018 en la empresa Laser Pharmaceutica S.A.S (2019)
This paper presents a proposal for the implementation of a management system in safety and health at work, in Laser Pharmaceutica S.A.S, based on the requirements of the NTC - ISO 45001:2018 and the Decree 1072 of 2015. The case study company has over 14 years of experience in the provision of quality control, for human, veterinary pharmaceuticals and cosmetics industry companies, among others. The proposal comes in response to the need for the company to implement strategies enabling it to become more competitive in the market, and provide greater confidence to their customers and other interested parties, as well as to comply with the legal requirement of safety and health at work management system.